Representasi Harapan Dalam Mv Bts “Spring Day” (Kajian Semiotika Roland Barthes) - Wahyuningratna, Ratu Nadya; Baskara Putri, Ratu Laura Mulia; Saputra, Windhi Tia (CommLine, 2023)
Every human being has hope in his life. they have a positive will, and can continue to be with the people they care about. This description of hope can be expressed in various ways, one of which is through a music video. One of the musicians who often brings up the theme of hope is BTS, they are considered to always be able to describe the life of teenagers in general, including the matter of hope and longing in life. One of their best works with the theme of hope is the Spring Day, which is predicted to tell about the Sewol Ferry incident that occurred in 2014. This song is an extraordinary achievement for BTS. From the beautiful song lyrics and music video cinematography, the writer finds several representations of hope by using Roland Barthes' Semiotics study.Keywords: BTS, hope, music video, semiotic, Spring Day